Cognitive-linguistic abilities and word segmentation in Braille - Nicolaiewsky, Clarissa de Arruda; Correa, Jane (Paidéia (Ribeirão Preto), 2009)
This study investigated the influence of cognitive and linguistic skills on unconventional written word segmentation in Braille of 21 students attending the first three years of the elementary school in an institution specialized in visual impairment. The ability to establish word boundaries in a text is developed during the long process of written language acquisition and plays an important role in text comprehension. The occurrence of hyposegmentation (junction of two or more words) and hypersegmentation (space incorrectly inserted in a word) was investigated in the written production of stories. Hyposegmentation was significantly more frequent than hypersegmentation. The students who presented a larger number of hyposegmentation performed worse in tasks of verbal ability, working memory, morphological awareness and reading, whereas those with fewer hyposegmentation occurrences performed better. The development of pedagogical activities focusing on cognitive and linguist abilities can favor the acquisition of Braille written language acquisition.